SOCIAL DISCRIMINATION AS PART OF THE PROCESS OF FORMING THE MAIN CHARACTERS SOCIAL IDENTITY IN THE NOVEL WONDER BY R.J. PALACIO - Meilyana Indi Rananda; Agnes Setyowati H; Ni Made Widisanti (Universitas Pakuan, 2020)
AbstractSocial discrimination is one of the problems that arises in the community from time to time. This study aims to describe the problem of social discrimination which is part of the process of forming social identity of the main character in the novel Wonder by R.J Palacio. Social discrimination experienced by the main character is caused by the genetic disorder he suffers. The analysis focuses on forms of social discrimination, the process of forming social identity that is formed through the existence of acts of social discrimination and the role of the family as a support system for the main character. Data processing in this analysis uses descriptive analysis methods and literature study techniques based on intrinsic and extrinsic elements. The result of the study shows that the form of discrimination received by the main character is direct discrimination and indirect discrimination, and that social discrimination experienced by the main character can be part of the formation of social identity if accompanied by family support.Keywords: social discrimination, family support, social identities, genetic disorders.